Comparison of the Complications and the Cost of Open and Laparoscopic Radical Nephrectomy in Renal Tumors Larger than 7 centimeters - Bayrak, Omer; Seckiner, Ilker; Erturhan, Sakip; Cil, Gokhan; Erbagci, Ahmet; Yagci, Faruk (Urology Journal, 2014)
Purpose: To compare the complications and the cost analysis of open radical nephrectomy (ORN) versus laparoscopic radical nephrectomy (LRN) in patients with renal tumors larger than 7 centimeters (cm). Materials and Methods: A retrospective analysis was performed in 173 patients (ORN group, n = 140; LRN group, n = 33) who underwent surgery for kidney tumors between 2008 and 2011. Patients’ age, tumor size, pre-operative surgical risk score (American Society of Anesthesiologists score), duration of hospitalization, complications and the costs of hospitalization were recorded. The complications in ORN group and LRN group were specified with Modified Clavien System in five grades. Results: The mean age was found 58.52 ± 13.74 years in ORN group, and 58.15 ± 12.81 years in LRN group (P = .847). Post-operative pain necessitating analgesics was observed in all patients (100%) after early post-operative period in both groups (Grade 1 complications). Blood transfusions were required in 51 patients (36.42%) in the ORN group, and 7 (21.21%) patients in the LRN group (Grade 2 complications) (P = .185). Grade 3 complication was not observed in each groups. Grade 4 complications were occurred in 6 (4.28%) patients [aortic injury, acute tubular necrosis, the need for dialysis, respiratory arrest (2), atrial fibrillation] in the ORN group, and in 1 (3.03%) patient (pulmonary embolism) in the LRN group. Grade 5 complication was occurred in 1 (0.71%) patient (death) in the ORN group. By the cost analysis, the average cost of ORN group was €1328, whereas €1508 in LRN group (P < .05). Conclusion: Laparoscopy is used in many clinics with an increasing frequency because of the improved patient comfort, better cosmetic results, less post-operative pain, lower transfusion rates, and early return to the daily activities. Besides these advantages, the negligible difference in the costs compared to the open surgery (mean difference = €180 per case) makes it even more attractive.